Gp120 substitutions at positions associated with resistance to fostemsavir in treatment-naive HIV-1-positive individuals. (19th March 2020) - Lepore, Luciana; Fabrizio, Claudia; Bavaro, Davide Fiore; Milano, Eugenio; Volpe, Anna; Lagioia, Antonella; Angarano, Gioacchino; Saracino, Annalisa; Monno, Laura
Abstract: Objectives: Fostemsavir, a novel attachment inhibitor targeting the HIV-1 gp120, has demonstrated wide in vitro activity. However, the high rate of HIV gp120 substitutions could jeopardize its efficacy. We investigated envelope ( env ) substitutions at positions associated with resistance to fostemsavir in patients with a new HIV-1 diagnosis according to HIV subtype and tropism. Methods: Gp120 sequences from 409 subjects were retrospectively analysed and the presence of the L116P, A204D, S375H/M/T, M426L, M434I and M475I mutations was evaluated. Other amino acid changes at the same positions were also recorded. The variability at each amino acid position was evaluated using Shannon entropy. Results: The frequency of mutations was: S375T (13.2%); M426L (6.8%); M434I (2.9%); M475I (2.7%); S375H (1.0%)/M (0.8%) and L116P (0.31%). Statistically significant differences were found at positions 375 (R5/non-R5 strains and B/non-B subtypes) and 426 (B/non-B subtypes); post hoc analysis revealed that significance for position 375 was steered by S375T while for position 426 significance was governed by unusual substitutions, in particular M426R (B/non-B, P  <   0.00001). The variability of env constant domains appeared to be more relevant in the non-B virus population. Conclusions: In conclusion, gp120 substitutions were detected in different subtypes and in both R5 and non-R5 variants. Despite the great variability of gp120, the frequency of mutations was low overall and the predominant substitution was S375T, the role of which in reducing fostemsavir efficacy is less substantial.